ANALYSIS OF ISLAMIC RELIGIOUS EDUCATION MATERIALS IN THE KURIKULUM MERDEKA FROM A SWOT PERSPECTIVE - Hidayah, Fathi; Setiawati, Lilis (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic Religious Education (PAI) is a compulsory subject at all levels of education in Indonesia, as regulated in PP No. 55 of 2007. In an effort to improve the quality of PAI learning, a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis is used to evaluate the implementation of the Independent Curriculum. This study used a qualitative method with PAI teacher participants at SMP Negeri 1 Blimbingsari. The results showed that the Independent Curriculum gives teachers the freedom to innovate in learning, but is constrained by limited resources and variations in implementation. The SWOT analysis identified opportunities such as strengthening religious values through collaboration with the community, as well as threats in the form of differences in curriculum interpretation. The resulting strategies include improving teacher professionalism, use of technology, and facility support. This study concludes the importance of synergy between teachers, the community, and educational institutions in supporting effective PAI learning that is relevant to the demands of the times.